Current apparent treatment‐resistant hypertension in patients undergoing peritoneal dialysis: A multi‐center cross‐sectional study. Issue 4 (2nd March 2022) - Li, Dan; Huo, Zhihao; Liu, Danyang; Gong, Nirong; Zhang, Fen; Kong, Yaozhong; Zhang, Yunfang; Su, Xiaoyan; Xu, Qingdong; Feng, Jiexia; Luo, Fuzhang; Wang, Cheng; et al.
Abstract: Apparent treatment‐resistant hypertension (aTRH) is the most commonly used term to report resistant hypertension (RH) and is considered as a common problem in dialysis population. However, few reports have focused on peritoneal dialysis (PD) hypertensive patients. The authors conducted a multi‐center cross‐sectional study involving 1789 PD patients from nine centers in Guangdong, China. The prevalence of aTRH was estimated by home blood pressure (BP) monitoring. Evaluating drug adherence through Eight‐item Morisky Medication Adherence Scale (MMAS‐8) and pill counting was performed to assess RH in one PD center. Related factors of aTRH were analyzed using logistic regression analysis. The prevalence of aTRH in PD patients was estimated at 42.2% (755 out of 1789 hypertensive patients) based on home BP. Of those, 91.4% patients were classified as uncontrolled RH, 2.0% as controlled RH, and 6.6% as refractory hypertension. The prevalence of RH was 40.6% and 41.9% among those with medium/high adherence based on the MMAS‐8 scores and the pill counting rate, respectively. PD patients who were younger, with higher body mass index, with lower serum albumin and poorer dialysis adequacy were significantly associated with higher aTRH incident. In conclusion, the present study demonstrates a high prevalence of aTRH in PD population, which occurs in about two in five treated hypertensive patients. Nutritional status and dialysis adequacy might tightly associate with aTRH.